Further Evaluation of a Practitioner Model for Increasing Eye Contact in Children With Autism. Issue 3 (May 2019) - Rapp, John T.; Cook, Jennifer L.; Nuta, Raluca; Balagot, Carissa; Crouchman, Kayla; Jenkins, Claire; Karim, Sidrah; Watters-Wybrow, Chelsea
Cook et al. recently described a progressive model for teaching children with autism spectrum disorder (ASD) to provide eye contact with an instructor following a name call. The model included the following phases: contingent praise only, contingent edibles plus praise, stimulus prompts plus contingent edibles and praise, contingent video and praise, schedule thinning, generalization assessments, and maintenance evaluations. In the present study, we evaluated the extent to which modifications to the model were needed to train 15 children with ASD to engage in eye contact. Results show that 11 of 15 participants acquired eye contact with the progressive model; however, eight participants required one or more procedural modifications to the model to acquire eye contact. In addition, the four participants who did not acquire eye contact received one or more modifications. Results also show that participants who acquired eye contact with or without modifications continued to display high levels of the behavior during follow-up probes. We discuss directions for future research with and limitations of this progressive model.